(untitled) (Web of Teachers: Inderscience Research, 2026)
The article shows that the methods of persuasion, persuasion and reprimand are effectively used in social advertising today, and that these types of advertising serve as an effective tool for manipulating the human mind, as well as the opinions and comments of linguistic scientists on social advertising. The role and importance of social advertising in today’s society are also illustrated from a theoretical and practical perspective using real-life examples.